To what extent have changes in channel capacity contributed to flood hazard trends in England and Wales? - Slater, L (Wiley, 2016)
The frequency of floods has been projected to increase across Europe in the coming decades due to extreme weather events. However, our understanding of how flood frequency is affected by geomorphic changes in river channel capacity remains limited. This paper seeks to quantify the influence of trends in channel capacity on flood hazards. Measuring and predicting the effect of geomorphic changes on freshwater flooding is essential to mitigate the potential effects of major floods through informed planning and response. Hydrometric records from 41 stream gauging stations were used to measure trends in the flood stage (i.e. water surface elevation) frequency above the 1% annual exceedance threshold. The hydrologic and geomorphic components of flood hazard were quantified separately to determine their contribution to the total trend in flood stage frequency. Trends in cross‐sectional flow area and mean flow velocity were also investigated at the same flood stage threshold. Results showed that a 10% decrease (or increase) in the channel capacity would result in an increase (or decrease) in the flood frequency of approximately 1.5 days per year on average across these 41 sites. Widespread increases in the flood hazard frequency were amplified through both hydrologic and geomorphic effects. These findings suggest that overlooking the potential influence of changing channel capacity on flooding may be hazardous. Better understanding and quantifying the influence of geomorphic trends on flood hazard will provide key insight for managers and engineers into the driving mechanisms of fluvial flooding over relatively short timescales